The Figure in Fine Art and Commercialism - Wooten, Christopher William (East Carolina University, 2011)
This body of sculpture is an exploration of the human figure through personal, public, and commercial works. The following thesis report will explore these various categories and how they play a role in the sculpture's aesthetic appearance, contextual meaning, and societal role. With each category comes an array of technical and conceptual challenges that must be solved in order for the sculpture to be a successful figure. My thesis will cover these various technical and conceptual approaches to modeling the figure, while also explaining how the intended overall purpose of the piece directly influences my choice in materials, scale, and sculptural style.
Keywords: Fine arts; Figures; Portraits; Sculpture; Figure sculpture; Human figure in art; Sculpture, American--North Carolina